Safety, feasibility, and prognostic value of stress perfusion CMR in patients with MR-conditional pacemaker. (10th October 2022) - Pezel, Théo; Lacotte, Jérôme; Horvilleur, Jérôme; Toupin, Solenn; Hovasse, Thomas; Unterseeh, Thierry; Sanguineti, Francesca; Said, Mina Ait; Salerno, Fiorella; Fiorina, Laurent; Manenti, Vladimir; Zouaghi, Amir; et al.
Abstract: Aims: To assess the safety, feasibility, and prognostic value of stress cardiovascular magnetic resonance (CMR) in patients with pacemaker (PM). Methods and results: Between 2008 and 2021, we conducted a bi-centre longitudinal study with all consecutive patients with MR-conditional PM referred for vasodilator stress CMR at 1.5 T in the Institut Cardiovasculaire Paris Sud and Lariboisiere University Hospital. They were followed for the occurrence of major adverse cardiovascular events (MACE) defined as cardiac death or non-fatal myocardial infarction. Cox regression analyses were performed to determine the prognostic value of CMR parameters. The quality of CMR was rated by two observers blinded to clinical details. Of 304 patients who completed the CMR protocol, 273 patients (70% male, mean age 71 ± 9 years) completed the follow-up (median [interquartile range], 7.1 [5.4–7.5] years). Among those, 32 experienced a MACE (11.7%). Stress CMR was well tolerated with no significant change in lead thresholds or pacing parameters. Overall, the image quality was rated good or excellent in 84.9% of segments. Ischaemia and late gadolinium enhancement (LGE) were significantly associated with the occurrence of MACE (hazard ratio, HR: 11.71 [95% CI: 4.60–28.2]; and HR: 5.62 [95% CI: 2.02–16.21], both P < 0.001). After adjustment for traditional risk factors, ischaemia and LGE were independent predictors of MACE (HR: 5.08 [95% CI: 2.58–14.0]; and HR: 2.28 [95% CI: 2.05–3.76]; both P < 0.001). Conclusion: Stress CMR is safe, feasible and has a good discriminative prognostic value in consecutive patients with PM. Graphical Abstract: Graphical Abstract